Argentina's Countercyclical Credit Policy Response: Macroprudential Regulation and Public Bank Credit during Covid-19 - Schclarek Curutchet, Alfredo (2020)
This chapter analyzes the countercyclical credit policy response in Argentina due to the Covid-19 pandemic. Specifically, the macroprudential regulations implemented by the Central Bank of Argentina (BCRA) to stimulate bank credits to micro-, small- and medium-sized enterprises (MSMEs) is examined. In addition, the specific credit response of the state-owned commercial bank, the Banco de la Nación Argentina (BNA), the biggest commercial bank in Argentina, is also scrutinized.